2021
DOI: 10.1002/aepp.13183
|View full text |Cite
|
Sign up to set email alerts
|

How women saved agricultural economics

Abstract: Women entered agricultural economics in numbers starting in the 1980s, and their ranks are increasing over time. We make the case that women have increased the relevance in the field of agricultural economics through their diverse interests, perspectives, and experiences. We document how women have changed the profession of agricultural economics in both academia and government. In research, women have expanded the field's treatment of non‐traditional topics such as food safety and nutrition and environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Women provided leadership both in scholarship and in institution building to support this new area of inquiry. Like Offutt and McCluskey (2022), however, we note that more needs to be done to expand diversity and representation from under-represented groups in this sub-field of agricultural economics. Many of the important questions in food safety and nutrition are most relevant to underserved communities, and new market performance questions have been raised by the inequalities in the food system laid bare by the 2020 global pandemic.…”
Section: Concluding Commentsmentioning
confidence: 91%
“…Women provided leadership both in scholarship and in institution building to support this new area of inquiry. Like Offutt and McCluskey (2022), however, we note that more needs to be done to expand diversity and representation from under-represented groups in this sub-field of agricultural economics. Many of the important questions in food safety and nutrition are most relevant to underserved communities, and new market performance questions have been raised by the inequalities in the food system laid bare by the 2020 global pandemic.…”
Section: Concluding Commentsmentioning
confidence: 91%
“…In these roles, they have served not only the profession but also as role models for other women entering the field. Although women have been under‐represented in some association‐related categories, particularly those relating to awards and recognition (see Offutt & McCluskey, 2022), we hope that a growing recognition of the many contributions made by women—bolstered by papers like this one—will lead to greater acknowledgement and recognition by the profession as a whole of the profound impact that ENRE women have had over the past four decades and will likely continue to have well into the future. Notably, of the six future challenges that McCalla et al (2010) identified for the AAEA through 2050, three fall clearly within the ENRE field (climate change, alternative energy sources, and resource depletion, degradation, and reallocation) and are areas where women have and will undoubtedly continue to play a critical role in meeting these challenges.…”
Section: Looking Behind and Ahead: Some Reflectionsmentioning
confidence: 99%
“…Since that time, research in ENRE has grown as an important component of agricultural economics research, to the point where, by 2017, over 30% of the articles published in the American Journal of Agricultural Economics (AJAE) were classified under the JEL Code for “Environmental Economics (Q5)” (Lybbert et al, 2018). 1 This increase parallels the increase in the share of members of the American Agricultural Economics Association (now Agricultural and Applied Economics Association (AAEA)) who are women, which rose from about 5% in 1980 to 34% in 2020 (Offutt & McCluskey, 2022). In fact, the interest of women in issues related to environmental protection and resource use was a key factor in the transformation of the AAEA from a male‐dominated association focused primarily on agricultural production, marketing, and finance to one that is broader and more inclusive, in terms of both interests and membership (Offutt & McCluskey, 2022).…”
mentioning
confidence: 99%
“…As Offutt and McCloskey (2022) mention, the occupational segregation literature suggests that women are relatively more attracted to public service because it better meets their preferences measured along a variety of employment attributes (Cortes & Pan, 2018). Shurchkov and Eckel (2018) review how employment outcomes sort according to behavioral traits, including gender differences in risk aversion, competitiveness, and willingness to negotiate.…”
Section: Public Service Making a Difference And Women's Careers In Ec...mentioning
confidence: 99%
“…Offutt and McCluskey (2022) also examine the literature to explain choices of specialties by men and women and the record for agricultural economists. They discuss how women led the expansion of agricultural economics from a focus on farm economics to a broader set of policies and markets encompassing food and the environment.…”
Section: Public Service Making a Difference And Women's Careers In Ec...mentioning
confidence: 99%